Impact of different oil gelators and oleogelation mechanisms on digestive lipolysis of canola oil oleogels. (December 2019) - Ashkar, Areen; Laufer, Sharon; Rosen-Kligvasser, Jasmine; Lesmes, Uri; Davidovich-Pinhas, Maya
Abstract: Oil structuring has been proposed as a promising strategy for fat replacement due to its solid texture and high unsaturation content. Oil structuring can be achieved using various gelator types, which induce oil gelation via various mechanisms. This research investigated the relation between the different gelators and gelation mechanisms, i.e. crystalline or polymer network, to the mechanical and rheological properties as well as their responsiveness to digestive lipolysis under simulated physiological conditions. Three gelators were examined with canola oil; ethyl cellulose (EC), mono- and di-glycerides (E471), and β-sitosterol + γ-oryzanol mixture. Generally, EC produced harder gels compared to E471 and softer gels compared to β-sitosterol + γ-oryzanol mixture. Similar trend was observed in the storage modulus at gel state. Temperature sweep rheology experiments detected an increase in modulus at gel state and gel point temperature with gelator concentration. Simulated intestinal lipolysis revealed a significantly different lipolysis pattern for the different gelation mechanisms. More specifically, EC based oleogels show similar susceptibility to lipolysis regardless of the polymer concentration, while β-sitosterol + γ-oryzanol mixture concentration reduced the rate and extent of free fatty acid release. E471 based oleogels showed high lipolysis levels up to 90% that was increased with gelator concentration suggesting gelator hydrolysis. Overall, the findings suggest that gelator type and gelation mechanism can be harnessed to engineer the mechanical properties and susceptibility to digestive lipolysis of custom-made oleogels. Graphical abstract: Image 1017 Highlights: Oleogel formulations using different structuring agents were studied. Oleogel hardness values in the order of E471 < EC < β-sitosterol + γ-oryzanol mixture was obtained. Thixotropy properties were found to be related to the oil structuring agent and gelation mechanism. Mechanical properties cannot be directly correlated to the oleogel lipolysis behavior.